2014
DOI: 10.1111/jog.12469
|View full text |Cite
|
Sign up to set email alerts
|

Lead and trace element levels in placenta, maternal and cord blood: A cross‐sectional pilot study

Abstract: Urban post-partum women and their neonates were at higher risk with elevated BLL. Estimate of cord blood Pb may not be the true index of neonatal BLL. These observations must be confirmed in a larger cohort because prenatal/neonatal screening avoids the risks associated with rest of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 9 publications
3
19
2
Order By: Relevance
“…In the present study the maternal BLLs mean was 10.31µg/dl which was higher than that reported by other studies such as study done in Karachi by Hakeem A on pregnant women in 2003 where the mean of BLLs was 9.9 (14) , study done in New York in 2005 by Zhu M et.al where maternal BLLs mean was 2.1 (11) , other study done in Iraq (Mousil city) where the mean was 3.2 (22) and study done in Iran in 2005 where the mean of BLLs was 9.9 (15) .These differences between results of these studies may be due to the differences ingestational age at which blood samples have been taken and methods used for detection of BLLs including commercial kits, atomic absorption spectrometry and inductively coupled plasma mass spectroscopy. Nevertheless, the result of current study still reveals higher level in study sample.…”
Section: Discussion:-contrasting
confidence: 69%
See 1 more Smart Citation
“…In the present study the maternal BLLs mean was 10.31µg/dl which was higher than that reported by other studies such as study done in Karachi by Hakeem A on pregnant women in 2003 where the mean of BLLs was 9.9 (14) , study done in New York in 2005 by Zhu M et.al where maternal BLLs mean was 2.1 (11) , other study done in Iraq (Mousil city) where the mean was 3.2 (22) and study done in Iran in 2005 where the mean of BLLs was 9.9 (15) .These differences between results of these studies may be due to the differences ingestational age at which blood samples have been taken and methods used for detection of BLLs including commercial kits, atomic absorption spectrometry and inductively coupled plasma mass spectroscopy. Nevertheless, the result of current study still reveals higher level in study sample.…”
Section: Discussion:-contrasting
confidence: 69%
“…The relationship between maternal blood lead levels and pregnancy out comes, includingmiscarriage, stillbirth, prematurity low birth weight andreduced head circumferences have had inconsistent results in studies (11)(12)(13)(14)(15)(16)(17) .Several studies were carried out in this concern,some of them found a significant association for example, study done by Xiex G in china 2013 (11) ,another done by Zhu M in New York 2008 (12) ,and study of ChelchowskaM,Ambroszkiewicz J in Poland 2013 (13) . Other studies found insignificant association such as study done by Hakeem A in Karachi 2003 (14) , Besharati A and Nasseri F in Islamic Republic of Iran 2005 (15) , study of MirghaniZ,Al-Rhashidi A in Saudi Arabia 2010 (16) , as well as study done by Rahman A in Kuwait 2012 (17) .…”
mentioning
confidence: 99%
“…In addition, a recent study of 78 women with suspected placenta accreta spectrum noted MRI confirmed an incorrect diagnosis or incorrectly changed a diagnosis based on ultrasonography in 38% of cases (39). Accordingly, MRI is not the preferred recommended modality for the initial evaluation of possible placenta accreta spectrum (40).…”
Section: Obstetric Care Consensusmentioning
confidence: 99%
“…Zinc is an essential trace mineral that is involved in many biological processes, including enzyme function, nucleic acid metabolism, cell signaling and apoptosis; it is necessary for growth and development, lipid metabolism, brain and immune function . Inherited deficiency and dietary factors that decrease the zinc bioavailability, play an important role in zinc deficiency . Zinc deficiency might decrease zinc concentrations in the hippocampus, induce irregular glucocorticoid production, and elicit neuropsychological symptoms such as emotional instability, isolation, irritability and depression …”
Section: Introductionmentioning
confidence: 99%